Regulation of Mouse Retroelement MuERV-L/MERVL Expression by REX1 and Epigenetic Control of Stem Cell Potency - Schoorlemmer, Jon; Pérez-Palacios, Raquel; Climent, Maria; Guallar, Diana; Muniesa, Pedro (Frontiers in Oncology, 2014)
About half of the mammalian genome is occupied by DNA sequences that originate from transposable elements. Retrotransposons can modulate gene expression in different ways and, particularly retrotransposon-derived long terminal repeats, profoundly shape expression of both surrounding and distant genomic loci. This is especially important in pre-implantation development, during which extensive reprograming of the genome takes place and cells pass through totipotent and pluripotent states. At this stage, the main mechanism responsible for retrotransposon silencing, i.e., DNA methylation, is inoperative. A particular retrotransposon called muERV-L/MERVL is expressed during pre-implantation stages and contributes to the plasticity of mouse embryonic stem cells. This review will focus on the role of MERVL-derived sequences as controlling elements of gene expression specific for pre-implantation development, two-cell stage-specific gene expression, and stem cell pluripotency, the epigenetic mechanisms that control their expression, and the contributions of the pluripotency marker REX1 and the related Yin Yang 1 family of transcription factors to this regulation process.